Digital technologies in education - Natalya Shumafovna Kozlova (Вестник Майкопского государственного технологического университета)
The article addresses one of the urgent problems - transformation of higher education in the conditions of digitalization. The article discusses the main directions of digital transformation, which radically changes the economy, education and lifestyle in general. It’s been shown that digital technologies are necessary for the educational process but not sufficient for increasing the effectiveness of academic work. The demand for the ability to analyze systems, dissemination of ideas and methods of process management, the increase in the number of workplaces where skills are required to set tasks and formalize methods for solving them - all these factors makes it necessary to redefine traditional educational results during the digital transformation of education. Achieving this goal is especially important due to the spread of cloud computing, public high-speed Internet, with the widespread introduction of smart digital tools, the use of artificial intelligence methods and the widespread introduction of virtual reality technology. Introduction of digital technologies has been studied that provides an opportunity to improve education, allowing planning concrete steps to transform the work of universities, as well as to improve educational and educational work. In order to cope with the approaching challenges, the Russian education system should implement a digital transformation in the shortest possible time, move to a new model of organization of the educational process, using high-tech organizational, pedagogical and methodological solutions. It’s been proposed to develop and widely implement highly efficient and cost-effective digital technologies. At the same time, it is necessary to overcome technological digital gap existing in education. The novelty of the research approach consists in identifying the main directions of transformation of the educational process at a university in the conditions of digital economy. As a result of the analysis, the author has developed a conceptual vision of the essence, perspectives and possible consequences of the transformation of modern education, revealed the main directions for introducing digital technologies of the educational process based on the use of digital technologies.